Havensville, Pottawatomie County - Mangus, Maggie (Kansas State University, The Chapman Center for Rural Studies, 2011)
A hundred years is enough time for at least three generations to flourish in the town. Serving as an important railroad center, Havensville supported many families and their businesses throughout the years, even reaching close to 500 inhabitants in 1900.
Maggie Mangus, “Havensville, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/39.
Keywords: Havensville; Our Heritage; Pottawatomie County; R.M. Croy; The Crow's Nest